IDENTIFIKASI FAKTOR-FAKTOR KEPUASAN KONSUMEN PDAM SEBAGAI DASAR PENENTUAN KEBIJAKSANAAN PENINGKATAN KINERJA PDAM DI KOTA SELONG KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT - Sahrul Ihsan (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
An Auditor's performance is highly demanded to always be able to provide guarantees for the preparation of financial statements in accordance with financial accounting standards and government accounting standards. To determine the accuracy of the auditor's performance itself various research criteria are used. In this study using Independence and Locus of Control as research criteria on the Performance of Internal Auditors. The population in this study was 68 people, 26 of whom worked as auditors, 42 staff and employees as assistant auditors for field inspection in the district inspectorate. The purpose of this study was to identify the factors of consumer satisfaction as the basis for determining policies to improve PDAM performance in the City of Selong East Lombok Regency of NTB and to analyze and determine which factors are priority considerations in order to improve the performance of PDAMs in Selong City, East Lombok. The results showed that (1). There are ten dimensions of service quality, namely: Reliability, responsibility, competence, access, courtesy, communication, credibility, security, understanding, and tangibles. (2). The implementation of all dimensions that build the quality of PDAM services in Selong City, East Lombok Regency in general does not meet consumer expectations, that is, it can only meet consumer expectations in the range of 49.41% to 69.09%. (3). Based on the factor analysis, it is obtained 4 factors that become priority decisions in an effort to increase consumer satisfaction. Factor 1, including the dimensions of responsibility, reliability and access. Factor 2, including the dimensions of courtesy and communication. Factor 3, including the dimensions of credibility, and understanding. Factor 4, including security dimensions. (4). There are a number of items that East Lombok PDAMs should consider in each dimension to increase customer satisfaction. Itams for reliability include the fulfillment of promises and the smooth working system. Responsibility includes the willingness, desire and readiness of employees to carry out tasks to help consumers meet their needs. East Lombok. The sampling technique in this study is saturated sample. The results showed that partially there was a positive influence of Independence and Locus of Control on Auditor Performance.